Sodobne meritve elektromagnetnih lastnosti protonov - Širca, Simon (Obzornik za matematiko in fiziko, 2008)
The proton is the simplest atomic nucleus that reveals its fundamental properties with a suitable probe, the high-energy electron beam. In the recent past, experimental investigations of the proton static structure end of the dynamical processes involving the proton have evolved rapidly. This paper describes two ways to study the electro-magnetic properties of protons: through measurements of elastic form-factors and electro-magnetic polarizabilities.
Keywords: atomsko jedro; elektromagnetizem; fizika; protoni; zgradba snovi